Chemical Profile of Ruta graveolens, Evaluation of the Antioxidant and Antibacterial Potential of Its Essential Oil, and Molecular Docking Simulations - Jianu, Călin; Goleț, Ionuț; Stoin, Daniela; Cocan, Ileana; Bujancă, Gabriel; Mișcă, Corina; Mioc, Marius; Mioc, Alexandra; Șoica, Codruța; Lukinich-Gruia, Alexandra Teodora; Rusu, Laura-Cristina; Muntean, Delia; et al. (Applied sciences, 2021)
The research aimed to investigate the chemical composition and antioxidant and antibacterial potential of the essential oil (EO) isolated from the aerial parts (flowers, leaves, and stems) of Ruta graveolens L., growing in western Romania. Ruta graveolens L. essential oil (RGEO) was isolated by steam distillation (0.29% v/w), and the content was assessed by gas chromatography-mass spectrometry (GC-MS). Findings revealed that 2-Undecanone (76.19%) and 2-Nonanone (7.83%) followed by 2-Undecanol (1.85%) and 2-Tridecanone (1.42%) are the main detected compounds of the oil. The RGEO exerted broad-spectrum antibacterial and antifungal effects, S. pyogenes, S. aureus, and S. mutans being the most susceptible tested strains. The antioxidant activity of RGEO was assessed by peroxide and thiobarbituric acid value, 1,1-diphenyl-2-picrylhydrazyl radical (DPPH), and β-carotene/linoleic acid bleaching testing. The results indicated moderate radical scavenging and relative antioxidative activity in DPPH and β-carotene bleaching tests. However, between the 8th and 16th days of the incubation period, the inhibition of primary oxidation compounds induced by the RGEO was significantly stronger (p < 0.001) than butylated hydroxyanisole (BHA). Molecular docking analysis highlighted that a potential antimicrobial mechanism of the RGEO could be exerted through the inhibition of D-Alanine-d-alanine ligase (DDl) by several RGEO components. Docking analysis also revealed that a high number RGEO components could exert a potential in vitro protein-targeted antioxidant effect through xanthine oxidase and lipoxygenase inhibition. Consequently, RGEO could be a new natural source of antiseptics and antioxidants, representing an option for the use of synthetic additives in the food and pharmaceutical industry.